Healthy Living Literacy Among STIE Ganesha Students - Imelda Rosadi; Syarif Hidayatullah; Haria Saputri; Hendra Candra; Zubair Arza; Aep Saefullah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research discusses various aspects of healthy living literacy, including the importance of maintaining a balanced diet, physical activity, and adequate amount of sleep, for a better quality of life. College students often face busy schedules and academic pressures, which can lead to unhealthy lifestyles, such as irregular diet, lack of exercise, and lack of sleep. This literacy serves as a guide for students to adopt a healthier lifestyle, which can improve their energy, focus and thinking ability. Students can be better prepared for academic and social challenges by applying the principles of healthy living. In the long run, healthy living literacy teaches students positive habits that will help them in their careers and daily lives. It is hoped that this literacy becomes part of the overall education so that students can live a healthy life. The purpose of this study is to provide an overview of the benefits of healthy living literacy as well as ways to implement a healthy lifestyle in the midst of a busy schedule. By having healthy life literacy, students can better prepare themselves to deal with academic pressures and other extraordinary life.